2022
DOI: 10.2196/32322
|View full text |Cite
|
Sign up to set email alerts
|

Improving a Mobile Telepresence Robot for People With Alzheimer Disease and Related Dementias: Semistructured Interviews With Stakeholders

Abstract: Background By 2050, nearly 13 million Americans will have Alzheimer disease and related dementias (ADRD), with most of those with ADRD or mild cognitive impairment (MCI) receiving home care. Mobile telepresence robots may allow persons with MCI or ADRD to remain living independently at home and ease the burden of caregiving. The goal of this study was to identify how an existing mobile telepresence robot can be enhanced to support at-home care of people with MCI or ADRD through key stakeholder inpu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…While our previous study ( 9 ) showed that those with MCI or early ADRD were able to provide overall feedback regarding the proposed assistive technology, when asked to imagine the assistance they may require in the future, they lacked future thinking capability in predicting their own future cognitive and functional abilities. Participants had a limited ability to independently identify potential cognitive challenges and suggest technology that could be of assistance for their future cognitive and functional declines.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…While our previous study ( 9 ) showed that those with MCI or early ADRD were able to provide overall feedback regarding the proposed assistive technology, when asked to imagine the assistance they may require in the future, they lacked future thinking capability in predicting their own future cognitive and functional abilities. Participants had a limited ability to independently identify potential cognitive challenges and suggest technology that could be of assistance for their future cognitive and functional declines.…”
Section: Discussionmentioning
confidence: 92%
“…For this brief report, we analyzed qualitative interview data collected in a previous study (July to August 2019) in which we obtained feedback on possible adaptations to a mobile telepresence robot and the robot’s potential utility from stakeholder groups, including patients with MCI or early ADRD ( 9 ). Approval from the Institutional Review Board at the Veterans Affairs (VA) Bedford Healthcare System (approval number 110818) was received.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations